Time-variant interest community based query message routing algorithm in opportunity social network - Junlei BI; Zhiyuan LI (Tongxin xuebao, 2019)
To solve the problem that the successful rate of resource query is low in opportunity social network,a query message routing algorithm based on time-variant interest community was proposed.Two well-known mobile social datasets were firstly analyzed,and then the temporal and spatial correlations of users were found.The time-variant interest communities based on temporal and spatial correlations of users were constructed.Next,a dynamic query routing on the constructed time-variant interest communities was proposed.Theoretical analysis shows that the proposed routing can run in O (nlog n) time.The comparisons between the proposed routing and state-of-the-art message delivery algorithms show that the proposed routing can keep high query success rate,reduce the average query latency and the hop count of a query and maintain low system overhead.